Samuel Johnson : A Survey and Bibliography of Critical Studies - Clifford, James L. (Book collections on Project MUSE., 1970)
For anyone interested in the work of Samuel Johnson and his place in eighteenth-century studies, this bibliography will be of great value, for it includes virtually everything of importance that has been written about Johnson from his own lifetime to the.